2015
DOI: 10.4236/asm.2015.52002
|View full text |Cite
|
Sign up to set email alerts
|

Does Male Circumcision Adversely Affect Sexual Sensation, Function, or Satisfaction? Critical Comment on Morris and Krieger (2013)

Abstract: Morris and Krieger (2013) have argued that male circumcision does not impact adversely on sexual sensation, satisfaction, and/or function. In the present paper, it is argued that such a view is untenable. By selectively citing Morris' own non-peer-reviewed letters and opinion pieces purporting to show flaws in studies reporting evidence of negative effects of circumcision, and by failing adequately to account for replies to these letters by the authors of the original research (and others), Morris and Krieger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Gregory Boyle, a psychologist with a track record of opposition to male circumcision, recently published a critique [2] of our systematic review. In essence, he disputed our high rating for two randomized controlled trials by scientists with strong track records and objected to the low rating we gave several studies with flawed study design, data interpretation and one-sided arguments.…”
Section: Introductionmentioning
confidence: 99%
“…Gregory Boyle, a psychologist with a track record of opposition to male circumcision, recently published a critique [2] of our systematic review. In essence, he disputed our high rating for two randomized controlled trials by scientists with strong track records and objected to the low rating we gave several studies with flawed study design, data interpretation and one-sided arguments.…”
Section: Introductionmentioning
confidence: 99%
“…A meticulously conducted systematic review of all studies found that, overall, MC had no adverse effect on penile sensitivity, sexual arousal, sexual sensation, or pleasure . Criticisms of that study were shown to lack merit . The findings were consistent with a systematic review of histological correlates of sexual sensation showing that the sensory receptors responsible for sexual pleasure (genital corpuscles) reside in the glans, not the foreskin, meaning loss of the foreskin by MC should not diminish sexual pleasure .…”
Section: Physical Harmmentioning
confidence: 54%
“…Several studies concluded that MC diminishes sexual pleasure for men and their female sexual partners. [131][132][133][134][135][136][137] Evaluation of these identified multiple flaws. 119,[138][139][140][141][142][143][144] Other studies, [145][146][147][148] including RCTs, [125][126][127]149 found MC had no adverse effect.…”
Section: Sexual Pleasurementioning
confidence: 99%
See 1 more Smart Citation
“…Evidently, many circumcised men feel so distressed about having been subjected to involuntary genital cutting as non-consenting infants or children, thereby depriving them of normal sexual responsivity, that they feel compelled to endure years of difficult and sometimes painful penile skin-expansion "foreskin restoration" efforts. Some passages in the preceding section have been adapted from Boyle[119].…”
mentioning
confidence: 99%